ODA A LAS MUSAS. HORACIO, CARM., III 4 - Ortega Carmona, Alfonso (Myrtia, 1994)
The Horace’s existence as a poet it’s held as testimony of the divine protection. The Muses protected him since his childhood and are considered as a symbol in his literary work. In Horace’s childhood Rome’s future is outlined: the civil wars difficulties are overcome, August warrants intelectual movements, Rome’s destiny is secured and, at the same time, the ruler’s political virtue of the ’consilium’ appears. This is the human virtue blessed by the gods and, the evil’s power in Hell, is a warning against disorder and chaos.